EFFECTIVENESS OF USING NATIVE SPEAKER IN TEACHING LISTENING COMPREHENSION - Sinta (UNMUH BABEL PRESS, 2020)
English should not be foreign to Indonesians anymore. English is not only open communication with the English but to almost all countries in the world. English is an international language, which now evolves into a medium of intellectual and social self- image. If not able to speak English well, especially young children then it will be outdated. Especially for academics whether it's students or lecturers, more in-depth references to science are mostly listed in English. listening is one of the skills that is considered difficult but 'neglected' when compared with other language skills such as speaking, reading, and writing. The difficulties encountered there are several reasons, including because English is a foreign language, which is different pronunciation, grammar and meaning. Especially when doing learning using native speakers, the students have trouble interpreting the intent of sound from audio that played. Native speaker is a person who has spoken the language in question from earliest childhood. Teaching the listening to most of the English lecturers is a huge challenge so that the success of a student in learning depends on the methods and teaching techniques that will be used by the lecturer in delivering the lecture material. Lecturers are required to be able to choose and present classroom learning materials using intensive teaching techniques, selective responsive, and so depending on the material he will convey.